Constructing Multi-Branches Complete Chaotic Maps That Preserve Specified Invariant Density - Weihong Huang (Discrete Dynamics in Nature and Society)
A general formulation for multi-branches complete chaotic maps that preserve a specified invariant density is provided and an implication relationship among this class of maps is revealed. Such relationship helps to derive a whole family of complete chaotic maps that preserve not only the same invariant measure but also the same degree of chaos in terms of Lyapunov component.